(untitled) (International Journal of Engineering and Computer Science, 2016)
Nano fluids are one of the combination of fluid and nano-sized solid particles which they are relatively used for some application. In general, nano fluids were used for various applications like heat transfer and solar energy applications. Nowadays the high usage of fossil fuel, which it is coming down in quantity in the earth. So we will go for alternate energy sources of solar, wind, tidal, etc. In a heat transfer system contain many losses, In order to overcome the losses, we will use some effectual heat transfer substance. So far reviews were done about nano fluids preparation, thermal conductivity, and performance. The main objective of this paper is to study about enhanced heat transfer in solar collector systems with the effect of various nano fluids.